Analisa Uji Kebergunaan Aplikasi Gojek Menggunakan System Usability Scale (SUS) - Dalai, Hastuti R; Nanja, M. (Jurnal Informatika UPGRIS, 2021)
The online motorcycle taxi application in Indonesia is an application created by a company engaged in transportation services, one of which is PT. Gojek Indonesia (GOJEK). In Gorontalo Province, GOJEK is focusing on cooperation with Bentor (motorcycle becak) which is one of the transportation used by the people of Gorontalo on a daily basis. Gojek collaborated with Bentor in May 2018, this shows that Gojek has only been used by the Gorontalo community. Because the Gojek application is still a new application for the Gorontalo community, there are still many people who are confused about using the application. Therefore, in this study a usability test is needed to measure the usefulness of the Go-Jek application based on the experience of the Gorontalo community, both those who become bentor drivers and the public who use this online transportation service. by using questionnaires and a usability scale (SUS) system that can be used to analyze data from the Gojek application usability test, the results of data analysis carried out using the Usability Scale (SUS) System, from 100 respondents using the Gojek application as general users the average value obtained given are 69 and 15 respondents who use the Gojek application as a driver, the average value given is 72, the two values obtained indicate that the application is a product or system that is categorized as Good. This is obtained based on the opinions given by users by filling out questionnaires. This shows that the Gojek application in the eyes of the user needs to be improved so that it is easy to understand and use, especially the Gojek user interface for general users. Because this is evidenced by the answers of 100 respondents to the questions symbolized by x, there are 16 people who answered agree, 8 people answered strongly agree and 7 people answered doubtfully that respondents need help from technical people to be able to use the Gojek application.